(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2015)
This theoretical analysis aimed to discuss the stance of the behavior analyst regarding to a behavior of the individual who owns the psychiatric diagnosis of schizophrenia, presenting a possibility to study this behavioral phenomenon and explanation of it, guided by focused on the science of behavior analysis. This science has an empirical approach to understanding and influencing the behavior of the individual. A brief critical analysis of causal attribution to biological variables commonly used to explain the schizophrenic is lifted without dis-regarding the importance of these variables for a science of behavior. It is not intended by this presentation, exhaust the topics. The deepening of the questions posed can be done by scrolling to the literature cited.